2017
DOI: 10.1371/journal.pone.0170616
|View full text |Cite
|
Sign up to set email alerts
|

VacA and CagA Status as Biomarker of Two Opposite End Outcomes of Helicobacter pylori Infection (Gastric Cancer and Duodenal Ulcer) in a Moroccan Population

Abstract: Helicobacter pylori (H. pylori) infection induces inflammation of the gastric mucosa, which may progress to precancerous lesions leading to gastric cancer. Pathological determinism is associated to some virulence genes of the bacterium, notably the vacA and cagA genes. The present study aimed to determine the H. pylori genotypes distribution and their association with sex, age and gastric diseases in a Moroccan population. Gastric biopsy was taken from 1079 consenting patients. The specimens were processed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
21
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 57 publications
(71 reference statements)
14
21
1
3
Order By: Relevance
“…pylori vacAi1 as a possible marker in the identification of patients at high risk of gastric cancer developing. The association of this allele with pre-neoplastic lesions confirms our previous result 10 and also the results obtained in a study conducted in Iran. 44 However, the results obtained for intestinal metaplasia lesions should be taken with caution, since H. pylori is hardly detectable in these lesions.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…pylori vacAi1 as a possible marker in the identification of patients at high risk of gastric cancer developing. The association of this allele with pre-neoplastic lesions confirms our previous result 10 and also the results obtained in a study conducted in Iran. 44 However, the results obtained for intestinal metaplasia lesions should be taken with caution, since H. pylori is hardly detectable in these lesions.…”
Section: Resultssupporting
confidence: 91%
“…The biopsies of these patients were previously used to characterize vacA-s, vacA-m, vacA-i regions and cagA 3 0 region polymorphism. 10,11 Therefore, in the present study, the correlation between vacA and cagA genotypes with histological lesions was established. Thus, all consenting patients had a personal interview before endoscopy, and were asked about individual characteristics.…”
Section: Patients and Samplingmentioning
confidence: 95%
See 1 more Smart Citation
“…We observed that there was a signi cant relationship between EPIYA-ABCCC and gastric cancer in Iranian population. Overall, it can be concluded that the higher number of EPIYA-C copy numbers leads to the higher risk of gastric cancer (55,88). Therefore, according to our results, it seems that the presence of EPIYA-ABCCC strains of H. pylori should be considered as an appropriate marker in prevention of gastric cancer in Iranian population.…”
Section: Discussionsupporting
confidence: 60%
“…Based on our statistical analysis, frequency of cagA gene in Iranian population was evaluated about 71.34%, which con rmed previous ndings. In addition, the presence of cagA has a meaningful relationship with gastrointestinal diseases such as peptic ulcer, gastric atrophy, and gastric cancer (54)(55). In our project, also, abundance of cagA positive strains in peptic ulcer and gastric cancer patients was very high, and we also saw a meaningful relationship between the presence of cagA gene and gastric cancer (ORs: 2.277; p-value: 0.00).…”
Section: Discussionsupporting
confidence: 59%